Pathways and progress to enhanced global sexually transmitted infection surveillance. - Melanie M Taylor; Eline Korenromp; Teodora Wi (PLoS Medicine)
Melanie Taylor and colleagues discuss global initiatives for surveillance of sexually transmitted diseases.